Can a Clinical Examination Demonstrate Intramuscular Tendon Involvement in Acute Hamstring Injuries?. Issue 10 (24th October 2017) - Crema, Michel D.; Guermazi, Ali; Reurink, Gustaaf; Roemer, Frank W.; Maas, Mario; Weir, Adam; Moen, Maarten H.; Goudswaard, Gert J.; Tol, Johannes L.
Background: Involvement of the intramuscular (central) tendon in acute hamstring injuries, as detected on magnetic resonance imaging (MRI), may prolong recovery times. To date, it is unclear whether hamstring injuries exhibiting intramuscular tendon involvement can be identified though routine clinical examinations that assess flexibility and strength. Purpose: To test whether MRI-detected intramuscular tendon involvement could be identified by a clinical assessment of muscle strength and flexibility. Study Design: Case-control study; Level of evidence, 3. Methods: Participants were drawn from a multicenter randomized controlled trial on the effect of platelet-rich plasma in acute hamstring injuries. Clinical parameters assessed within 5 days of injury were active knee extension and passive straight-leg raise for hamstring flexibility and isometric knee flexion force with 15° and 90° of knee flexion. Also, 1.5-T MRI of the thigh was performed within 5 days of injury and was evaluated for the presence of different types of intramuscular tendon involvement. One-way analysis of variance was used to determine whether clinical parameters could discriminate injuries with intramuscular tendon involvement from those without such involvement. Results: A total of 74 acute hamstring injuries were included, with 52 (70.3%) injuries affecting the myotendinous junction. Injuries exhibiting intramuscular tendon discontinuity on MRI had an increased mean absolute flexibility deficit for active knee extension (20.4° ± 14.9° vs 10.7° ± 9.0°, respectively; P = .006) and decreased mean strength at 15° (62.2 ± 26.7 N vs 76.6 ± 22.5 N, respectively; P = .05) compared with injuries without intramuscular tendon discontinuity. Flexibility and strength showed major overlap and variance among injuries with and without intramuscular tendon involvement. Conclusion: Hamstring flexibility and strength cannot be used to discriminate the presence of intramuscular tendon involvement.